Роль науково-дослідної роботи при підготовці фахівця-енергетика - Попова, Ірина Олексіївна; Popovа, Iryna (Суми : СумДПУ ім. А. С. Макаренка, 2025)
UA: У роботі розглядаються питання місії, цілі і задачі студентського науково-дослідного гуртка, організаційна структура науково-дослідної роботи здобувачів у закладах вищої освіти, умови, форми і методи ведення занять з гуртківцями для ефективної гурткової роботи здобувачів та керівника. EN: The paper examines the issues of the mission, goals and objectives of a student research group, the organizational structure of research work of applicants in higher education institutions, the conditions, forms and methods of conducting classes with group members for effective group work of applicants and the supervisor.
The Role of Research Work in the Training of an Energy Specialist
Keywords: наукова гурткова робота; завдання; форми; методи ведення занять у кружку; scientific group work; tasks; forms; methods of conducting classes in a group